New Uzbekistan and Third Renaissance as A National Idea (Eurasian Journal of Learning and Academic Teaching, 2022)
This year, on first of September, Uzbekistan celebrated its 30th anniversary of gaining Independence. Since the first days of Independence, Uzbekistan has been consistently carrying out large-scale reforms in the political, socio-economic and other spheres. These reforms are based on their own long-term development strategy, which has been recognized in the world as an Uzbek Model. As our First President Islam Karimov said, "Not a single nation, not a single country in the world was given an easy way to achieve independence, the very opportunity to breathe freely, to build their own destiny and future with their own hands." In addition, today there are many examples of our greatest achievements over the past period. Undoubtedly, we would like to note the great contribution of Islam Karimov to the development of Uzbekistan and its Independence